Improving Revisit Intention Through Physical Evidence and Tourist Experience (Case Study at Water World Jatiluhur) - A N Kusumadewi; A Mawardi; P Patoni; A D Riana (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to see the effect of Physical Evidence as place attractiveness in increasing Revisit Intention on tourists and to what extent the influence of Tourist Experience felt by the tourists can affect Revisit Intention in Jatiluhur Water World tourism object. This research uses a quantitative research model, with the method used is descriptive quantitative method and a sample of 100 respondents from tourists who have visited Jatiluhur Water World.. The study shows that Physical Evidence has significant effect on Revisit Intention, then the Tourist Experiences significantly affects the increase of tourists in Revisit Intention in Jatiluhur Water World. and for the both variables, Physical Evidence and Tourist Experience significantly influence Revisit Intention for the tourists of Jatiluhur Water World tourism object. Physical Evidence and Travel Experience have a significant effect on Revisit Intetion on Jatiluhur Water World tourists